Serum measurement of muscle and oxidative damage in soccer players after a game - Cleber Aurino de Pinho; Débora da Luz Scheffer; Ricardo Aurino Pinho; Paulo Cesar Silveira; Tiago Cesar Silveira; Luciano Acordi da Silva; Cláudio Teodoro de Souza; Cleber de Medeiros (Universidade Federal de Santa Catarina, 2010)
Futsal is a sport that requires sudden acceleration and deceleration with abruptchanges in direction. The marked impacts experienced by futsal players lead to muscle andoxidative damage. The objective of this study was to evaluate the serum levels of markers ofmuscle and oxidative damage in futsal players after a game. Six players with a mean age of 21.2± 0.98 years, weight of 67.1 ± 5.5 kg and height of 171.0 ± 0.07 cm participated in this study.Measurements were obtained 30 minutes before game 1 (pre-game), immediately after game 1(post-game 1), and immediately after a second game (post-game 2), which was performed 24hours after game 1. Serum was collected for the evaluation of creatine kinase and of damageto proteins and lipids. Creatine kinase concentrations, lipid peroxidation (xylenol) and proteincarbonylation were significantly higher after games 1 and 2 when compared to pre-game values.Sulfhydryl levels were lower after the end of games 1 and 2 compared to pre-game values. Nodifference in any of the parameters analyzed was observed between post-game 1 and post-game2. Taken together, the results demonstrate that a futsal match provokes muscle and oxidativedamage. Surprisingly, no increase in the parameters studied was observed after game 2. In viewof the limited knowledge about the time of recovery after a futsal match, this study may provideimportant information to professionals working with this sport.